2017
DOI: 10.1371/journal.pone.0169877
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of DNA Extraction Method on the Representation of Human Oral Bacterial and Fungal Communities

Abstract: The application of high-throughput, next-generation sequencing technologies has greatly improved our understanding of the human oral microbiome. While deciphering this diverse microbial community using such approaches is more accurate than traditional culture-based methods, experimental bias introduced during critical steps such as DNA extraction may compromise the results obtained. Here, we systematically evaluate four commonly used microbial DNA extraction methods (MoBio PowerSoil® DNA Isolation Kit, QIAamp®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 30 publications
11
109
0
5
Order By: Relevance
“…Of course, PCR and sequencing artefacts may have affected these estimates (Leray & Knowlton, ). A common strategy to limit these effects is the exclusion of low‐abundance sequences or OTUs (Elbrecht & Leese, ; Vesty et al., ), yet our estimates were derived from OTU clustering with singleton sequences excluded, and further removal of OTUs with abundances <5 resulted in very similar conclusions. A more conservative filtering approach enabled by individually indexed PCRs is to exclude OTUs based on their occurrences in multiple PCRs (Alberdi et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, PCR and sequencing artefacts may have affected these estimates (Leray & Knowlton, ). A common strategy to limit these effects is the exclusion of low‐abundance sequences or OTUs (Elbrecht & Leese, ; Vesty et al., ), yet our estimates were derived from OTU clustering with singleton sequences excluded, and further removal of OTUs with abundances <5 resulted in very similar conclusions. A more conservative filtering approach enabled by individually indexed PCRs is to exclude OTUs based on their occurrences in multiple PCRs (Alberdi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding analyses involve a series of methodological decisions that are likely to affect measures of biodiversity (Alberdi, Aizpurua, Gilbert, & Bohmann, 2017;Dickie et al, 2018;Murray, Coghlan, & Bunce, 2015). The effects of DNA extraction methods on DNA yield and detected microbial community composition have been examined for substrates including oral and rumen samples (Henderson et al, 2013;Vesty, Biswas, Taylor, Gear, & Douglas, 2017), permafrost (Vishnivetskaya et al, 2014), and soils (Delmont et al, 2011;Kang & Mills, 2006;Wagner, Praeg, Reitschuler, & Illmer, 2015). In soils, the detection of prokaryote communities is affected by site-specific factors such as spatial heterogeneity and the propensity of cells and molecules to adsorb to soil particles (Lombard, Prestat, van Elsas, & Simonet, 2011), sample size (Kang & Mills, 2006), and extraction method (Delmont et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study on matched oral samples directly compared the fungal DNA signatures detected when using a variety of different DNA preparation methods. Fungal signatures proved to be more sensitive to DNA isolation methods than bacterial signatures (Vesty et al, 2017). To directly assess the relative efficiency of recovering DNA from different fungi and how this might skew signatures, we tested isolation and analysis approaches using model libraries of known ratios of 4 fungi commonly found in intestinal samples (Tang et al, 2015).…”
Section: Challenges In Defining the Mycobiotamentioning
confidence: 99%
“…While genomic content extraction methods have been developed for bacteria in microbiome analyses, they are generally inefficient for fungi due to the nature of their rigid cell walls, which cannot be easily lysed. A recent study evaluating DNA extraction methods from saliva samples demonstrated that diversity of fungi, unlike that of their bacterial counterparts, is heavily influenced by the method employed (Vesty, Biswas, Taylor, Gear, & Douglas, ). Based on our experiences and other comparative studies of DNA extraction methods (Halwachs et al, ; Huseyin, Rubio, O'Sullivan, Cotter, & Scanlan, ), at least an extra bead‐beating step is required to ensure mechanical lysis of fungal cell walls for effective genomic content recovery.…”
Section: How We Can Study the Mycobiome?mentioning
confidence: 99%